Knowledge and Attitudes Toward Organ/Tissue Donation and Transplantation Among Health Care Professionals Working in Organ Transplantation or Dialysis Units - (:unkn) unknown (ELSEVIER SCIENCE INC, 2011)
Objective. To evaluate the awareness and attitudes of health care professionals toward organ/tissue donation and transplantation. Methods. We included 309 health care professionals from 27 dialysis centers and eight organ transplantation centers in Istanbu in the present study conducted from April 2008 to August 2008. The 24-item questionnaire, including items concerning sociodemographic features and knowledge about and attitudes toward organ/tissue donation and transplantation, was applied by face-to-face interviews. Results. An organ/tissue donation card was completed among 77% of subjects, while 90% were identified as supporting transplantation. The main reasons identified for lack of donation were lack of confidence (59.7%), fear of procurement (31.5%), and inappropriate use of harvested organs (18.1%). Conclusion. In conclusion, targeting health care professionals in the first place and development of nationwide media and educational campaigns on the ethical, moral, as well as religious dimensions of transplantation and donation seem crucial to increase the number of individuals who can act as role models via their positive impact on the general public's attitudes toward organ donation.
Keywords: PERSONNEL; STUDENTS; HOSPITALS